Implikasi Sustainable Development Goals di Indonesia: Perspektif Riset Akuntansi dan Ekonomi - Dosinta, Nina Febriana; Kurniasih, Erni Panca; Kartika, Metasari (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
Sustainable development is essential for the continuity of companies and economic activities. This research investigates the implications of Sustainable Development Goals (SDGs) in Indonesia by reviewing previous research and filling gaps using accounting and economic perspectives. This research adopted a systematic literature review and content analysis approach using 13 articles from published articles indexed by the Science and Technology Index (SINTA) 2 and 3. Research findings, namely the variable presence of a Corporate Social Responsibility Officer or Sustainability Officer, appear to be a predictor of SDGs disclosure in corporate reporting. The following research finding is that educational accountants as educational curriculum creators can align with SDGs. Another research finding, Zakat plays a role in achieving SDGs, namely poverty, hunger, health, and education.